Cooking energy choices in urban areas and its implications on poverty reduction - Kitole Felician A.; Tibamanya, Felister Y.; Sesabo, Jennifer K. (International Journal of Sustainable Energy Volume 42, 2023 - Issue 1, 2024)
A research article submitted to the International Journal of Sustainable Energy Vol. 42. No.1. of 2023.